THE INTERPLAY OF ANXIETY, LEARNING STRATEGIES AND STUDENTS’ READING COMPREHENSION - Multazam Abubakar (Universitas Islam Negeri Alauddin Makassar, 2020)
Anxiety is one of factors under affective domain which influences the successfulness of language learning. The aims of this study were to identify the level of anxiety experienced by the students while studying and to investigate the extent to which the students’ anxiety contributes to their reading performance. The research was carried out in the second grade students of a junior high school. The design of this study was correlational research. The data were collected using three instruments: Foreign Language Reading Anxiety Scale (FLRAS), Young Learners’ Language Strategy with Survey questionnaire and reading test. The data were analyzed with questionnaire frequency test and regression analysis. The result indicated that the students’ anxiety level was 65.633 which indicated that they experienced high level of anxiety. To test the effect of learning strategies to as intervening variable in the relationship between anxiety as independent variable and students’ reading comprehension as dependent variable, past analysis was used. Regression coefficient of direct effect, that is the correlation between anxiety and learning strategies, was 0.190; while indirect effect, that is the correlation between anxiety on reading comprehension through learning strategies, was -0.069. The result implied that that learning strategies do not mediate the correlation between anxiety and reading comprehension. Therefore, the anxiety does not affect learning strategies to improve students’ reading comprehension. The findings of this study might be used as input to teachers and students in an effort to create effective classroom environment.